Some unpleasant general equilibrium implications of executive incentive compensation contracts - John B. Donaldson; Natalia Gershun; Marc P. Giannoni (Federal Reserve Bank of New York, 2011)
We consider a simple variant of the standard real business cycle model in which shareholders hire a self-interested executive to manage the firm on their behalf. A generic family of compensation contracts similar to those employed in practice is studied. When compensation is convex in the firm's own dividend (or share price), a given increase in the firm's output generated by an additional unit of physical investment results in a more than proportional increase in the manager's income. Incentive contracts of sufficient yet modest convexity are shown to result in an indeterminate general equilibrium, one in which business cycles are driven by self-fulfilling fluctuations in the manager's expectations that are unrelated to the economy's fundamentals. Arbitrarily large fluctuations in macroeconomic variables may result. We also provide a theoretical justification for the proposed family of contracts by demonstrating that they yield first-best outcomes for specific parameter choices.
Keywords: E32; J33; 330; delegation; executive compensation; indeterminacy and instability